(untitled) (TRANSFORM: Journal of English Language Teaching and Learning, 2023)
This study dealt with deixis on Mandok Hata in Saur Matua Death Ceremony. The objectives of the study were to identify the deixis types, to evaluate the realization the use of deixis and to explain the reason for using deixis on Mandok Hata in Saur Matua Death Ceremony. This study was conducted by using descriptive qualitative design. The sources of data were taken from VCD of Saur Matua. The technique for analyzing the data is descriptive qualitative research. The results of this research showed that the total numbers of deixis classification were 82. There were person deixis (37.80%), place deixis (1.22%), time deixis (7.32%), discourse deixis (3.66%), and social deixis (50%). The use of social deixis became the most dominant types after person deixis of deixis classification. The realization of deixis found on Mandok Hata in Saur Matua was depend the situation in which language is used that affect both how participants used language and how it is received. The reason why deixis used based on the realization of deixis.